ARTIFICIAL INTELLIGENCE AND CENTRAL ECONOMIC PLANNING - Pejković, Marko (Serbian political thought, 2025)
In this paper, the author will attempt to elaborate and complement the existing arguments about the impossibility of artificial intelligence (AI) ever enabling centralized efficient economic planning at the state level in the form of government plan. The rapid development of AI and other technologies in recent years has reawakened the debate about the upcoming technical capacities that could perhaps in the near future overcome all the weaknesses of centralized economic planning known from the previous century. However, the lack of conceptual prerequisites in the domain of AI that are necessary for successful centralized planning actually argues in favor of the fact that even any experiment on this topic is both scientifically and economically unjustified. The introductory part of the paper provides an overview of the main concepts and dilemmas within the debate, the next part discusses mathematical paradoxes as conceptual obstacles to economic planning with the help of AI (the problem of self-reference), while the final part of the paper will be a critique of the attempts of AI ideologists-architects to overcome these obstacles through the eventual fusion of humans and AI machines.